APPLICATION OF SOLAR FEED FERMENTOR TECHNOLOGY TO IMPROVE THE EFFICIENCY OF FERMENTED FEED PRODUCTION AT BALEBAT FARM, KALIJAYA VILLAGE - Pratiwi, Laras; Wulansari, Putri Dian; Supriatman, Agus; Widyastuti, Titin; Kurniawan, Anri (LPPM Univ. Ibn Khaldun Bogor, 2026)
The limited availability of feed during the dry season has been a major constraint for smallholder dairy goat farmers in Kalijaya Village, Ciamis Regency. Farmers traditionally rely on fresh fodder without preservation, resulting in low feed efficiency and unstable milk production. This community service program introduced the Solar Feed Fermentor System, a renewable energy-based technology designed to support sustainable fermented feed production. The implementation involved 20 farmer participants and included stages of socialization, training, mentoring, and evaluation. Results showed a significant improvement in farmers’ knowledge and technical skills, with average understanding scores increasing from 62% to 86%. Feed production capacity increased from 20–30 kg/day to 120–150 kg/day, while processing time and energy costs were reduced by more than 50%. The adoption of solar energy minimized dependence on electricity and promoted environmentally friendly practices. This program demonstrates a replicable model of community empowerment integrating renewable energy, feed technology, and rural sustainability.